2021
DOI: 10.3390/cancers13184716
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Homologous Recombination Deficiency in Pancreatic Cancer

Abstract: Pancreatic cancer is a treatment-resistant malignancy associated with high mortality. However, defective homologous recombination (HR), a DNA repair mechanism required for high-fidelity repair of double-strand DNA breaks, is a therapeutic vulnerability. Consistent with this, a subset of patients with pancreatic cancer show unique tumor responsiveness to HR-dependent DNA damage triggered by certain treatments (platinum chemotherapy and PARP inhibitors). While pathogenic mutations in HR genes are a major driver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 195 publications
(271 reference statements)
0
10
2
Order By: Relevance
“…Our data are partially consistent with the recently published analyses that demonstrated inconsistent results of predictive value of other HR/FA genes mutations as biomarkers of platinum response. 37 In contrast, in our study, ATM mutations were rather common (18/543 – 3.3%). Moreover, ATM inhibitors are currently in clinical trials.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Our data are partially consistent with the recently published analyses that demonstrated inconsistent results of predictive value of other HR/FA genes mutations as biomarkers of platinum response. 37 In contrast, in our study, ATM mutations were rather common (18/543 – 3.3%). Moreover, ATM inhibitors are currently in clinical trials.…”
Section: Discussioncontrasting
confidence: 87%
“… 44 However, other studies did not confirm the role of family history as a surrogate marker of platinum efficacy. 37 Although the role of family history as a predictor of higher risk of mutations in HR/FA genes cannot be denied, our study failed to confirm this issue. We assume that the results of our study are related to the insufficient knowledge of family history by patients in our population.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Reduced, DNA-damaged, induced nuclear RAD51 foci have been associated with BRCA1 or BRCA2 gene defects and PARPi responses [ 110 , 111 ]. This approach is currently under investigation, and functional assays have not yet been validated for pancreatic cancer [ 112 ].…”
Section: The Challenge Of Testing: Searching For Hrd Scarmentioning
confidence: 99%
“…Retrospective and systematic analyses have found that 15–25% of PDAC have mutations in genes associated with HRD and that there were no significant differences between somatic and germline mutations [ 114 , 115 , 116 ]. Historically, sensitivity of cancers with HRD to platinum chemotherapy have been well characterized, specifically owing to the inability for HRR-deficient cells to resolve DNA damage induced by platinum therapy [ 117 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%